PEMETAAN AREA PERSAWAHAN DENGAN PENDEKATAN GIS UNTUK MENDUKUNG PENGEMBANGAN EKOWISATA DI DESA ADAT SIBETAN, KARANGASEM BALI - Putu Aryastana; I Wayan Gde Erick Triswandana; Made Mas Surya Wiguna; Putu Angga Bagus Setyawan; Tegar Wibawa (Universitas Warmadewa, 2024)
The community service project in Subak Gantalan aimed to identify land use conditions and update the existing irrigation network scheme to support the development of eco-tourism based on natural beauty and education on Bali's traditional irrigation system. Based on the results of the inventory survey and digitization, it was found that land use in Subak Gantalan consists of 9.38% for buildings, 86.96% for rice fields and farming activities, and 3.66% for vegetation or gardens. The irrigation network scheme update aimed to assist farmers in efficiently managing water distribution, ensuring optimal water availability for crops, and supporting the sustainability of the agricultural system. The analysis of the mapping results and the updated irrigation network scheme revealed significant potential for eco-tourism development in this area. Several strategies have been identified to realize this potential, including strengthening supporting infrastructure such as constructing tourist paths and providing educational information for visitors. Additionally, involving the local community in managing tourism activities is a key factor in ensuring the sustainability of eco-tourism and ensuring that the local community feels economic benefits. With the right strategies, the development of eco-tourism in Subak Gantalan will not only support cultural and environmental preservation but also create new sustainable income sources for the local population. The results of this community service project demonstrate that Subak Gantalan has great potential to be developed as a sustainable, community-based eco-tourism destination.